Trends in measles vaccination in Nigeria and implications for childhood blindness - A E Aghaji (International Journal of Medicine and Health Development, 2017)
Background: Measles is an important cause of childhood death and cornealblindness in Africa, and measles immunisation is important in reducing childhood mortality and morbidity. Many countries in sub-Saharan Africa still have challenges with achieving high immunisation coverage. In Nigeria there are intra-national disparities in vaccination coverage. Objectives: The objectives of this study are to explore trends in immunisation coverage in Nigeria and assess the relationship between measles immunisation coverage and causes of childhood blindness in Nigeria. Methods: Data from the Nigerian National Demographic and Health Survey (NDHS) 1990-2013 were utilized. In addition, data on published population based childhood blindness surveys in three geographical zoneswere obtained. Secondary analyses of data were done using STATA V.12.1 (Statcorp, Texas). The prevalence of measles immunisation coverage indicators was stratified by regional and individual level variables Results: Nigeria's currentmeasles immunization coverage is 42%. The greatest coverage recorded was in 46% in 1990, but declined soon after due to political reasons. The reduced coverage was strongly associated with poverty, lack of mother's education, geographical location and corneal blindness (p < 0.05). Conclusion: Measles immunisation coverage in Nigeria is low and inequitable. There is need to develop strategies to increase mothers' education and socioeconomic status in order to develop sustainable models for childhood measles vaccination in Nigeria.